Effect of maropitant, a neurokinin‐1 receptor antagonist, on the minimum alveolar concentration of sevoflurane during stimulation of the ovarian ligament in cats. (13th February 2013) - Niyom, Sirirat; Boscan, Pedro; Twedt, David C; Monnet, Eric; Eickhoff, Jens C
Abstract Objective Determine if maropitant decreases the minimum alveolar concentration (MAC) of sevoflurane during stimulation of the ovarian ligament in cats. Study design Prospective study. Animals Fifteen, female cats weighing 2.5 ± 0.6kg (mean ± SD). Methods Anesthesia was induced and maintained with sevoflurane. The right ovary was accessed via laparoscopy. A suture around the ovary and ovarian ligament was exteriorized through the abdominal wall for stimulation. A stimulus–response curve was created to identify the optimal force for MAC comparisons. In 10 cats, MAC was determined with only sevoflurane (baseline) then after 1 and 5 mg kg−1 intravenous maropitant administration. The stimulation tension force used was 4.9 N. Repeated measures anova was used to compare the groups. MAC was defined as the average of the cross‐over concentrations and reported MAC is adjusted to sea‐level and depicted as mean ± SD. Results The stimulus‐response curve was hyperbolic and plateaued at 4.3 ± 3 N. The optimal tension force chosen to compare MAC was 4.9 N. The baseline sevoflurane MAC was 2.96 ± 0.3%. Maropitant, 1 mg kg−1, decreased the MAC to 2.51 ± 0.3% (15%, p < 0.01). The higher maropitant dose of 5 mg kg−1 did not change MAC further when compared to the low dose (2.46 ± 0.4%, p = 0.33). Conclusion and clinical relevance The ovarian ligament stimulation model is suitable to determine MAC during visceral stimulation in cats. Maropitant decreased the anesthetic requirements during visceral ovarian and ovarian ligament stimulation in cats. Maropitant (1 mg kg−1) decreases MAC by 15%; a higher dose had no additional effect.